Burden of illness for super-refractory status epilepticus patients. (2nd January 2017) - Beg, Jamil M.; Anderson, Thomas D.; Francis, Kevin; Meckley, Lisa M.; Fitzhenry, David; Foster, Todd; Sukhtankar, Susheel; Kanes, Stephen J.; Moura, Lidia M. V. R.
Abstract: Objective: To provide an estimate of the annual number of super-refractory status epilepticus (SRSE) cases in the US and to evaluate utilization of hospital resources by these patients. Methods: The Premier Hospital Database was utilized to estimate the number of SRSE cases based on hospital discharges during 2012. Discharges were classified as SRSE cases based on an algorithm using seizure-related International Classification of Diseases-9 (ICD-9) codes, Intensive Care Unit (ICU) length of stay (LOS), and treatment protocols (e.g. benzodiazepines, anti-epileptic drugs (AEDs), and ventilator use). Secondary analyses were conducted using more restrictive algorithms for SRSE. Results: A total of 6, 325 hospital discharges were classified as SRSE cases from a total of 5, 300, 000 hospital discharges. Applying a weighting based on hospital characteristics and 2012 US demographics, this projected to an estimated 41, 156 cases of SRSE in the US during 2012, an estimated incidence rate of ∼13/100, 000 annually for SRSE in the US. Secondary analyses using stricter SRSE algorithms resulted in estimated incidence rates of ∼11/100, 000 and 8/100, 000 annually. The mean LOS for SRSE hospitalizations was 16.5 days (median =11; interquartile range [IQR] = 6–20), and the mean ICU LOS was 9.3 days (median =6; IQR =3–12). The mean cost of an SRSE hospitalization was 51, 247 (median = 33, 294; 95% CI = 49, 634–52, 861). Limitations: The analysis uses ICD-9 diagnostic codes and claims information, and there are inherent limitations in any methodology based on treatment protocol, which created challenges in distinguishing with complete accuracy between SRSE, RSE, and SE on the basis of care patterns in the database. Conclusion: SRSE is associated with high mortality and morbidity, which place a high burden on healthcare resources. Projections based upon the findings of this study suggest an estimated 25, 821–41, 959 cases of SRSE may occur in the US each year, but more in-depth studies are required.